2023
DOI: 10.3390/cancers15082260
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Restoration Modulates the Microbiome in Inflammation-Driven Colorectal Cancer

Abstract: Chronic inflammation of the colon (colitis) is a known risk factor for inflammatory-driven colorectal cancers (id-CRCs), and intestinal microbiota has been implicated in the etiology of id-CRCs. Manipulation of the microbiome is a clinically viable therapeutic approach to limiting id-CRCs. To understand the microbiome changes that occur over time in id-CRCs, we used a mouse model of id-CRCs with the treatment of azoxymethane (AOM) and dextran sodium sulfate (DSS) and measured the microbiome over time. We inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
5
1
Order By: Relevance
“…This indicated a reduction in the prevalence of pathogenic bacterial genera such as Aeromonas and Anaeroplasma , which have the potential to induce intestinal inflammation. 79 , 80 However, the CRC microbiome in both groups did not appear substantially affected by neoadjuvant therapy as compared to patients who did not receive neoadjuvant therapy prior to surgical resection. Additional prospective studies are needed to explore this further.…”
Section: Discussionmentioning
confidence: 88%
“…This indicated a reduction in the prevalence of pathogenic bacterial genera such as Aeromonas and Anaeroplasma , which have the potential to induce intestinal inflammation. 79 , 80 However, the CRC microbiome in both groups did not appear substantially affected by neoadjuvant therapy as compared to patients who did not receive neoadjuvant therapy prior to surgical resection. Additional prospective studies are needed to explore this further.…”
Section: Discussionmentioning
confidence: 88%
“…Microbiome manipulation, through fecal material transplant or probiotic treatment, can improve locomotor outcomes in animal models of SCI ( Zhang et al, 2018 , Kigerl et al, 2016 ), however we are the first to identify and propose a role for a specific bacteria in the etiology of chronic abdominal pain and dysfunction after SCI. Specifically, Anaeroplasma , a gram-negative bacteria characterized as pathogenic ( Jing et al, 2021 ), was increased in chronic SCI and is significantly increased in human patients with inflammation-driven colorectal cancer ( Chen et al, 2021 ), irritable bowel syndrome presenting with constipation ( Gates et al, 2023 ), and Crohn’s disease ( Choo et al, 2022 ) highlighting the potential involvement of this microbe in diseases with overlapping symptom profiles to NB.…”
Section: Discussionmentioning
confidence: 99%
“…It is a fact that chronic colonic inflammation is a risk factor for CRC. In this context, studies have shown a relative higher abundance of Anaeroplasma in colitis mouse models with decrease in levels following healthy gut microbiome transfer [ 47 ]. Other studies have shown a higher abundance of Anaeroplasma in mutated APC gene mouse models than controls.…”
Section: Abnormal Gut Microbiome In Patients With Colorectal Cancermentioning
confidence: 99%
“…Besides the abovementioned bacteria, there are many others that have shown associations with CRC. One study showed an increased prevalence of Akkermansia in longstanding colitis models [ 47 ]. Another study performed on humans analyzing the oral microbiome showed a decreased prevalence of Prevotella in the CRC vs. healthy group [ 69 ].…”
Section: Abnormal Gut Microbiome In Patients With Colorectal Cancermentioning
confidence: 99%